Web service integration — a goal based approach - Xiong, Lu Ying. (2008)
The objective of this research project is to investigate how Goal Net can assist the agent for the purposes of web service integration. A Graphical User Interface for Goal Net modeling is prototyped, and a XML-based interchange format for both Goal Net Graphical User Interface Editor and Goal Net agent is also proposed. The practice of the proposed methodology of converting the business process logic into GNML is demonstrated through sample case studies.